KINERJA KARYAWAN BALAI LATIHAN KERJA DIUKUR DARI PENGEMBANGAN KARIR, MOTIVASI, DAN PELATIHAN - Anton Subyantoro; Supriyono Supriyono (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
The purpose of this study was to determine: 1) The Effect of Work Motivation on Employee Performance, 2) The Effect of Job Training on Employee Performance, 3) The Effect of Career Development on Employee Performance, 4) The Effect of Work Motivation, Job Training, and Career Development on Employee Performance. This research was conducted on employees of the Tulungagung Regency Work Training Center (BLK). In this study using quantitative research, the population is 48 employees. The sampling technique used was the saturated sampling technique, namely the determination of the sample in which all members of the population were used as samples. Data collection techniques using a closed questionnaire method that has been tested with validity and reliability tests. The data analysis technique used is multiple linear regression,. The results of this study indicate that partially 1) Work Motivation has an effect on Employee Performance. Motivation is a form of attention from superiors or co-workers to employees, this attention can improve employee performance. 2) Job Training has an effect on Employee Performance. An employee participating in Job Training will gain knowledge or insight about the work in their field, so that their performance will increase. 3) Career Development affects Employee Performance. Career development is very influential on his performance because of this, he can plan his future career where he works so that performance can be optimal according to goals. 4) Work Motivation, Job Training, and Career Development have an effect on Employee Performance. The results of this study can be used as input and consideration for the management of the Tulungagung Regency Work Training Center (BLK) to improve employee performance by improving the quality of human resources.